Academic mobility of Russian students on the international education market - Puzanova Zh.V., Larina T.I., Narbut N.P., (Opción, 2019)
The aim of this article is to describe the dynamics of changes in the position of Russian students in the context of international mobility. Data have been obtained by the method of the questionnaire survey and by focus groups. As a result, the percentage of Russian students involved in international educational processes, the countries which attract the largest number of Russian students as well as programmes they want to study, the obstacles to international mobility and other data have been obtained. In conclusion, interest in studying abroad among Russian students is still high.